2010
DOI: 10.1002/jsfa.4077
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of a marine oligopeptide preparation from Chum Salmon (Oncorhynchus keta) on radiation‐induced immune suppression in mice

Abstract: We propose that MOP be used as an ideal adjuvant therapy to alleviate radiation-induced injuries in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
4
12
0
Order By: Relevance
“…MOP groups, the white cell counts were not significantly augment compared with the IR control group, although slight increases were observed. These results are consistent with our other data [13] in that WBI of mice do cause an exponential decline in cell survival of splenic cells and a depression capable of the response of splenic mononuclear cells to mitogens, both concanavalin A and lipopolysaccharide, and MOP can alleviate these inhibition effects. Considering these findings, we conclude that MOP possesses good irradiation protection property, which partly attributes to their strong immunostimulative activity.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…MOP groups, the white cell counts were not significantly augment compared with the IR control group, although slight increases were observed. These results are consistent with our other data [13] in that WBI of mice do cause an exponential decline in cell survival of splenic cells and a depression capable of the response of splenic mononuclear cells to mitogens, both concanavalin A and lipopolysaccharide, and MOP can alleviate these inhibition effects. Considering these findings, we conclude that MOP possesses good irradiation protection property, which partly attributes to their strong immunostimulative activity.…”
Section: Resultssupporting
confidence: 93%
“…MOP caused a decline of 18% in the apoptosis rate of splenocytes ( P < 0.05). The result was similar to the findings of our other studies [13] in that MOP treated group significantly impaired the radiation-induced changes of levels of apoptosis-related proteins. Taken together, these results demonstrate that treatment with MOP protects the mitochondrial membrane against radiation-induced immune cell damage and genetic damage.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our studies and those of others revealed atrophy of the hematopoietic tissues, a decrease in WBC counts, and immune dysfunction in fish and mammals during the first few days after radiation [5, 14, 15, 3335]. In this study, fish exposed to γ-radiation for 1 week showed a significant decrease in the total number of WBCs.…”
Section: Discussionsupporting
confidence: 75%
“…Radiation is an important environmental factor with hazardous effects on health, including oxidative stress [1,2], hematopoietic system dysfunction [3], genetic mutations [4] and immune dysfunction [5]. Ionizing radiation (IR) administered during radiotherapy generates free radicals when it passes through living tissues.…”
Section: Introductionmentioning
confidence: 99%